2020
DOI: 10.1111/scs.12877
|View full text |Cite
|
Sign up to set email alerts
|

Nursing professional practice environment and its relationship with nursing outcomes in intensive care units: a test of the structural equation model

Abstract: Introduction Burnout, intention to leave and ultimately shortage of skilled nurses are associated with poor practice environments; however, in Iran comprehensive data are unavailable. The aim of this study was to investigate the relationships between the nursing professional practice environment with nurses’ burnout and intention to leave in intensive care units, using structural equation modelling analysis. Methods This cross‐sectional, multi‐centred study was conducted among 320 nurses in twenty ICUs of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
(33 reference statements)
0
16
1
Order By: Relevance
“…The result confirmed adequate construct validity of the MBI. (7) Ethical considerations. The study was approved by the Research Ethics Committee of Shiraz University of Medical Sciences (No: IR.SUMS.…”
Section: Olson's Hospital Ethical Climate Survey (Hecs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The result confirmed adequate construct validity of the MBI. (7) Ethical considerations. The study was approved by the Research Ethics Committee of Shiraz University of Medical Sciences (No: IR.SUMS.…”
Section: Olson's Hospital Ethical Climate Survey (Hecs)mentioning
confidence: 99%
“…( 4 ) Nursing practice environment characteristics including resource inadequacy, poor inter-professional collaboration, and lack of supportive management are associated with nurses’ job burnout. ( 7 ) The prevalence of burnout is estimated to range from 10%-70% among nurses and 64% of Chinese nurses experienced job burnout. ( 4 ) In Iran, the overall prevalence of nursing burnout has been reported to be 25%.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was corroborated by a study with 320 ICU nurses in Iran that reported high levels of burnout in the participants, with a rate of emotional wearing of 70% and a rate of only 49% of personal fulfillment. Professional wearing showed a directly significant relationship with intention of leaving nursing (25) .…”
Section: Discussionmentioning
confidence: 92%
“…Intensive care units (ICUs) are facing increasing work pressure due to their high workload, high number of patients per nurse, increased recording and the care of critically ill and unstable patients (Adams et al, 2019;Rivaz et al, 2021). Numerous international studies have reported high numbers of ICU nurses expressing their intention to leave, including 24% in Canada (Sawatzky et al, 2015), 30% in the Netherlands (van Dam et al, 2013), 41.1% in the USA (Fitzpatrick et al, 2010) and 48.9% in China (Lai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%